Particle size distributions in the Eastern Mediterranean troposphere - N. Kalivitis (Atmospheric Chemistry and Physics, 2008)
Atmospheric particle size distributions were measured on Crete island, Greece in the Eastern Mediterranean during an intensive field campaign between 28 August and 20 October, 2005. Our instrumentation combined a differential mobility particle sizer (DMPS) and an aerodynamic particle sizer (APS) and measured number size distributions in the size range 0.018 μm–10 μm. Four time periods with distinct aerosol characteristics were discriminated, two corresponding to marine and polluted air masses, respectively. In marine air, the sub-μm size distributions showed two particle modes centered at 67 nm and 195 nm having total number concentrations between 900 and 2000 cm−3. In polluted air masses, the size distributions were mainly unimodal with a mode typically centered at 140 nm, with number concentrations varying between 1800 and 2900 cm−3. Super-μm particles showed number concentrations in the range from 0.01 to 2.5 cm−3 without any clear relation to air mass origin. A small number of short-lived particle nucleation events were recorded, where the calculated particle formation rates ranged between 1.1–1.7 cm−3 s−1. However, no particle nucleation and growth events comparable to those typical for the continental boundary layer were observed. Particles concentrations (Diameter <50 nm) were low compared to continental boundary layer conditions with an average concentration of 300 cm−3. The production of sulfuric acid and its subsequently condensation on preexisting particles was examined with the use of a simplistic box model. These calculations suggested that the day-time evolution of the Aitken particle population was governed mainly by coagulation and that particle formation was absent during most days.